Living Systems, Complexity & Information Systems Science - Knight, Shirlee-ann; Halkett, Georgia (Association for Information Systems, 2010)
The paper examines some of the significant new developments in the epistemological framing of systems theory, and their application within the information and management sciences. Specifically, the article argues that Information Systems (IS) – at its heart a systems-science – requires an ongoing discourse into how the metaphors of ‘living systems’, ‘complex systems’, and ‘complexity’ apply to the theoretical foundations of the IS discipline at large.Pragmatically, the implications of developing a complex and living systems framework to investigate IS phenomena has the capacity to synthesise the very way information systems researchers consider their discipline, and the scientific inquiry of it. The “information system” becomes a decentralised, complex and evolving entity, where notions of chaos theory; system self-organisation; autopoietic and dissipative networks; emergence; entropy; and nonlinear dynamics; provide a rich and novel way to investigate system behaviours, human cognitive behaviours, and the management and business contexts in which those behaviours occur.